The Design of a Smart Livestock Monitoring System - Firdaus, Ananda Ade (PT. Lentera Ilmu Publisher, 2025)
The livestock industry faces challenges in maintaining animal health, productivity, and welfare due to reliance on manual observation and delayed detection of health issues. This study aims to design a smart livestock monitoring system that leverages modern technologies to support farmers with timely, data-driven decision-making. The proposed system integrates sensor-based data collection, wireless communication, and a centralized platform for processing and visualization. Through this approach, key parameters such as animal health, activity patterns, and environmental conditions are monitored in real time. The results demonstrate that the system minimizes manual workload, reduces the risk of unnoticed illnesses, and enhances overall resource utilization. The main contribution of this study is the development of an affordable, scalable, and user-friendly system that empowers farmers, including those in small- and medium-scale operations, to adopt digital solutions for sustainable livestock management.